Effects of chitosan coating on cell membrane oxidation and ethylene production in Huanghua pear fruit (Pyrus pyrifolia var.) - SHUI Mao-xing; MA Guo-rui; CHEN Mei-ci; WANG Qiang (浙江大学学报. 农业与生命科学版)
The changes of cell membrane oxidation and ethylene production were measured in Huanghua pear fruit (Pyrus pyrifolia var.) coated with chitosan at normal temperature storage. The results indicated that the activity of Superoxide dismutase (SOD) was relatively strong with chitosan treatments, the activity of Lipoxygenase (LOX) was very weak, the stability of cell membrane became great, the content of Malondialdehyde (MDA) reduced remarkably, the rate of ethylene production was very low and its climax was no distinctness. However, the activity of SOD declined rapidly without chitosan treatments, the activity of LOX was extremely strong in early and late fruit storage, the rate of ethy lene production was very high and it reached its peak on the 11 th day after being picked.